Twice lost, twice found: A new species of Gonolobus (Apocynaceae: Asclepiadoideae) with a reappraisal of the genus in the Yucatan Peninsula Biotic Province - Carnevali, Germán; Romero-González, Gustavo A.; Tapia-Muñoz, José Luis; Ramírez-Morillo, Ivón M.; Ramírez-Díaz, Claudia J.; Cetzal-Ix, William; Duno De Stefano, Rodrigo; Romero-Soler, Katya J. (Phytotaxa, 2022)
Gonolobus is reassessed in the Yucatan Peninsula Biotic Province (YPBP). The genus consists of seven taxa in the area: six species and two subspecies. These include a taxon that we propose here as a new species and the treatment of G. yucatanensis as a subspecies of G. stenanthus and the new combination G. stenanthus subsp. yucatanensis is proposed. These two taxa are endemic to the YPBP. The other species are G. barbatus (for which we propose a lectotype), G. cteniophorus, G. fraternus, G. glaberrimus, and G. leianthus. The new species is G. caamalii Carnevali & R. Duno, restricted to the Yucatán state in Mexico and distinguished by its corolla lobes with a dark purple (almost black) longitudinal, callose band along the proximal 2/3 on the right side of the lobes and a 1.1–1.3 mm broad, annular, continuous dark purple-black band surrounding the gynostemium and corona at the base of the corolla lobes. It appears related to G. leianthus from southern Megamexico, a species from humid forests at higher elevations and that differs in its larger flowers with broader corolla lobes and a strikingly different color pattern in the flowers. The new species is described, illustrated, and discussed. Entries for all Gonolobus species from the YPBP include a brief discussion and specimen citations. The conservation status of the Gonolobus taxa endemic to the YPBP are assessed either as as Endangered (EN) or as Near threatened (NT). Distributional maps for all Gonolobus from the area covered are presented. Finally, we offer a key to Gonolobus of the YPBP.